2023
DOI: 10.1038/s41531-023-00448-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI data-driven clustering reveals different subtypes of Dementia with Lewy bodies

Abstract: Dementia with Lewy bodies (DLB) is a neurodegenerative disorder with a wide heterogeneity of symptoms, which suggests the existence of different subtypes. We used data-driven analysis of magnetic resonance imaging (MRI) data to investigate DLB subtypes. We included 165 DLB from the Mayo Clinic and 3 centers from the European DLB consortium and performed a hierarchical cluster analysis to identify subtypes based on gray matter (GM) volumes. To characterize the subtypes, we used demographic and clinical data, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Longitudinal patterns of atrophy could improve our understanding of the role of sex along the disease course. In this context, the role of sex in DLB heterogeneity should be elucidated, for example aligning with recent studies on disease subtypes based on MRI measures (40).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Longitudinal patterns of atrophy could improve our understanding of the role of sex along the disease course. In this context, the role of sex in DLB heterogeneity should be elucidated, for example aligning with recent studies on disease subtypes based on MRI measures (40).…”
Section: Discussionmentioning
confidence: 87%
“…This avenue is of further interest to advance our current knowledge about the less investigated 'olfactory bulb only' pathological subtype of DLB (39). We recently showed that atrophy in olfactory cortex is one of the brain regions that best discriminates between a DLB subtype with widespread predominant cortical atrophy and a DLB subtype with predominant fronto-occipital atrophy (40). Hence, the interplay between sex, age, and heterogeneity in regional atrophy and clinical phenotype in DLB deserves future investigation.…”
Section: Discussionmentioning
confidence: 98%
“…13 Findings thus support the claim that occipital damage may be an early signature of the whole DLB spectrum. 14 We acknowledge that this study has some limitations, mainly related to its cross-sectional single-center design and limited sample size. One limitation of the study relies on the age difference between patients and controls; all the analyses were conducted adjusting for age effect, but the sample was limited in size for a proper matching without constraining the statistical model.…”
Section: Discussionmentioning
confidence: 94%
“…A number of recent studies have searched for endophenotypes within DLB to delineate the influence of the various neuropathologies [39,40]. Disentangling the influence of respective neuropathies to allow a precision medicine approach is of increasing importance with the advent of DMTs aiming to target specific neuropathological changes.…”
Section: Challenges In Clinical Trialsmentioning
confidence: 99%
“…A number of recent studies have searched for endophenotypes within DLB to delineate the influence of the various neuropathologies [39,40]. Disentangling the influence of respective neuropathies…”
Section: Neuropathological Heterogeneitymentioning
confidence: 99%